C# 7 and .NET Core 2.0 recipes - Loukas, Dimitris (Packt, 2017)
"C# is a multi-paradigm programming language providing support for software engineering principles such as strong type checking, array bound checking, automatic garbage collection, and more. C# 7 comes with a host of new features to build powerful cross-platform applications. Also, the ASP.NET is the web application framework through which you can develop web applications. In this course, you will learn everything you need to know to start developing applications using the newest features that come with C# 7 as well as the newest version of the .NET Core. The course will start with a quick introduction to C# and .NET that will prepare you for what comes next. You will then learn about the new features of C# 7. Following that, you will get in-depth knowledge of ASP.NET Core along with the new version of the Entity Framework. Next, we will discuss some more advanced concepts of C# like delegates, lambda expressions, and LINQ. From this course, you'll learn newest features of C# and ASP.NET. You'll be developing the web applications with ASP.NET. Also, learn the advanced C# programming concepts."--Resource description page